Causes and management of secondary postpartum haemorrhage in a tertiary medical college hospital in Bangladesh - Nessa, Kamrun; Bari, Sumia; Khan, Sanjida; Sultana, Ferdowsi; Akbar, Tania (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Globally postpartum haemorrhage remains a leading cause of maternal death. It affects only 1-2% of postnatal women. This low incidence of secondary PPH and linkage to maternal morbidity rather than mortality was the reason for the little attention among obstetricians, but it is recently gaining importance and interest with the increase morbidity and mortality related to secondary PPH. Methods: A retrospective study was conducted on the diagnosed patients of secondary PPH admitted in Enam Medical College and Hospital, Dhaka, Bangladesh, from January 2015 to December 2016. Among 33 cases of secondary PPH age of the patients, parity, mode of delivery, causes and management were noted from medical records. All data was analyzed by SPSS16. Results: Among 33 patients 14 (42.4%) were primi and 19 (57.6%) were multipara, age between 18 to 38 years, majority admitted 2nd and 3rd week after delivery. Among 33 patients 12% delivered vaginally at home and 30% vaginally at hospital and 58% undergone LUCS. We found 34% retained bits of placenta, 27% uterine wound dehiscence, 24% retained clots and 15% endometritis as causes. Less than 3 units blood needed in 22 (66.7%) patients and 11 (33.3%) needed more than 3 units. About 6 (18%) patients were treated conservatively, MVA were needed in 18 (55%) patients, repair of wound in 4 (12%) and TAH was in 5 (15%). Conclusions: Secondary PPH is increasing may result in significant maternal morbidity as well as mortality. More study needed to identify the risk factors and causes to reduce maternal mortality and morbidity.